2016
DOI: 10.1016/j.sajb.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The coastal red-milkwood ( Mimusops caffra ) seed: Proximate, mineral, amino acid and fatty acid composition

Abstract: Mimusops caffra is an indigenous fruit-bearing tree in the coastal dune forests on the eastern coastline of South Africa. The tree is endangered by communities who use it for fuel-wood and construction timber. In an effort to promote sustainable utilisation of M. caffra, we evaluated the potential of its seed as a source of nutrients and cottage industry raw materials by determining the seed's proximate, mineral, fibre and amino acid composition and the seed oil's fatty acid profile. The seed had a gross energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Studies have shown that, depending on total lipid content and fatty acid composition, agroindustrial residues present great potential for extraction of good quality oil, which is rich in bioactive compounds (phytosterols, tocopherols, carotenoids), with good yield for food and pharmaceutical industry and even for biofuel production (Luzia & Jorge 2013). Oils extracted from agro-industrial wastes have showed similar physicochemical characteristics to conventional edible oils (soybean, sunflower, corn), so they can be used as a source of oil extraction for use in food preparations (Chivandi et al 2016).…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…Studies have shown that, depending on total lipid content and fatty acid composition, agroindustrial residues present great potential for extraction of good quality oil, which is rich in bioactive compounds (phytosterols, tocopherols, carotenoids), with good yield for food and pharmaceutical industry and even for biofuel production (Luzia & Jorge 2013). Oils extracted from agro-industrial wastes have showed similar physicochemical characteristics to conventional edible oils (soybean, sunflower, corn), so they can be used as a source of oil extraction for use in food preparations (Chivandi et al 2016).…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…During the industrial processing of T. ferdinandiana fruits, the seeds are treated as waste products and have been discarded. Recent studies on many fruit seeds or kernels have shown that they have the potential to be utilized as ingredients for value addition, they are very nutritious and could be used as alternate sources of essential minerals, fatty acids, and proteins [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been naturalized and is widely distributed in South Africa, it is an imported weed native to several tropical African countries, such as Botswana, Eswatini, Kenya, Mozambique and Zimbabwe [34]. In South Africa, G. fruticosus is found across several provinces, including Mpumalanga, the North West, KwaZulu-Natal, Eastern Cape, Western Cape and Limpopo [41].…”
Section: Distribution and Occurrence Of The Selected Medicinal Plantsmentioning
confidence: 99%